2020
DOI: 10.1210/endocr/bqaa193
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Is Essential for Survival Through Frog Metamorphosis

Abstract: Thyroid hormone (TH) is required for frog metamorphosis, and corticosterone (CORT) increases TH signaling to accelerate metamorphic progression. However, a requirement for CORT in metamorphosis has been difficult to assess prior to the recent development of gene editing technologies. We addressed this long-standing question using TALEN gene disruption to knock out pomc (proopiomelanocortin) and disrupt CORT production in Xenopus tropicalis. As expected, mutant tadpoles had a reduced peak of plasma CORT at meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…Therefore, we provide evidence that upregulation of circulating levels of CORT and GC receptors play roles in enhancing the survival of larval amphibians exposed to salinity. CORT‐dependent increases in thyroid hormone are necessary for organ development and survival through metamorphosis (Shewade et al, 2020), and CORT expedites the development of larval amphibians in unfavorable conditions (Denver, 1999; Hayes & Wu, 1994). Although most studies of survival focus on metamorphosing amphibians, our study demonstrates that CORT directly enhances survival for larvae exposed to increased salinity, a chronic anthropogenic stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we provide evidence that upregulation of circulating levels of CORT and GC receptors play roles in enhancing the survival of larval amphibians exposed to salinity. CORT‐dependent increases in thyroid hormone are necessary for organ development and survival through metamorphosis (Shewade et al, 2020), and CORT expedites the development of larval amphibians in unfavorable conditions (Denver, 1999; Hayes & Wu, 1994). Although most studies of survival focus on metamorphosing amphibians, our study demonstrates that CORT directly enhances survival for larvae exposed to increased salinity, a chronic anthropogenic stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we provide evidence that upregulation of circulating levels of CORT and GC receptors play roles in enhancing the survival of larval amphibians exposed to salinity. CORTdependent increases in thyroid hormone are necessary for organ development and survival through metamorphosis (Shewade et al, 2020), and CORT expedites the development of larval amphibians in unfavorable conditions (Denver, 1999;Hayes & Wu, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from Dan Buchholz's laboratory in which they inactivated the gene that codes for GR using CRISPR/Cas9 genome editing in X. tropicalis showed that GR is essential for survival through metamorphosis ( Sterner et al, 2020 ). This same group inactivated the gene that codes for proopiomelanocortin, the precursor for ACTH and other bioactive peptides, and found that the tadpoles did not survive metamorphosis, but this defect could be rescued by treatment with CORT ( Shewade et al, 2020 ).…”
Section: Neuroendocrine Control Of Amphibian Metamorphosismentioning
confidence: 99%
“…Glucocorticoids represent an ancillary endocrine influence on metamorphosis, regulating the rate at which it proceeds by altering sensitivity of target tissues to TH and modulating the expression of TH-regulated genes (Sachs and Buchholz, 2019). The significance of the role of GCs is underscored by the requirement of both CORT and GR for survival and completion of metamorphosis in Xenopus (Shewade et al, 2020;Sterner et al, 2020). Expression of several TR target genes can be induced by TCDD and other AHR agonists, and TCDD exposure can alter tail resorption and limb growth during metamorphosis (Taft, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%